Effect of dental bleaching on pulp oxygen saturation in maxillary central incisors - a randomized clinical trial - Lima, Lorena Ferreira; Alencar, Ana Helena Gonçalves de; Decurcio, Daniel de Almeida; Silva, Julio Almeida; Favarão, Isabella Negro; Loureiro, Marco Antônio Zaiden; Barletta, Fernando Branco; Estrela, Carlos (Journal of Applied Oral Science, 2019)
Objective: To assess pulp oxygen saturation levels (SaO2) in maxillary central incisors after dental bleaching. Materials and Methods: 80 participants (160 teeth) were randomly allocated to four groups: G1 In-office bleaching with two applications of 35% hydrogen peroxide (HP) (20 minutes), followed by at-home bleaching with 10% carbamide peroxide (CP) (2 hours/day for 16 days); G2 - Same protocol as G1, plus desensitizing toothpaste; G3 - Inoffice bleaching with 35% HP and one application of placebo gel (20 minutes), followed by at-home bleaching with 10% CP (2 hours/day for 16 days); and G4 - Same protocol as G3, plus desensitizing toothpaste. Pulp SaO2 levels were measured before (T0) and immediately after (T1) in-office bleaching; on the 5th (T2), 8th (T3), 12th (T4), and 16th days of at-home bleaching (T5); and on the 7th (T6) and 30th (T7) days. Mean (SD) pulp SaO2 levels were compared within groups by generalized estimating equations (GEE) and Student’s t-test (P<0.05). Results: Mean pulp SaO2 at T0 was 84.29% in G1, 84.38% in G2, 84.79% in G3, and 85.83% in G4. At T1, these values decreased to 81.96%, 82.06%, 82.19%, and 81.15% in G1, G2, G3, and G4 respectively, with significant difference in G4 (P<0.05). During home bleaching, pulp SaO2 levels varied in all groups, with 86.55%, 86.60%, 85.71%, and 87.15% means at T7 for G1, G2, G3, and G4, respectively; G2 presented significant difference (P<0.05). Conclusions: Pulp SaO2 level in maxillary central incisors was similar at baseline, reducing immediately after in-office bleaching, regardless of using desensitizing toothpaste and increasing at 30 days after dental bleaching.